Pengaruh Model Learning Cycle 7E terhadap Keterampilan Generik Sains Siswa pada Materi Pencemaran Lingkungan di SMP NEGERI 1 Balongan Indramayu - Anilia Ratnasari; Risti Maulidah (Mangifera Edu, 2018)
Generic science skills of students are still rarely measured by teachers and learning models Learning Cycle 7E was still rarely applied by teachers as a model of learning in schools, then conducted research with the aim to determine the effect of learning cycle model 7E on generic skills science students on environmental pollution material in SMP Negeri 1 Balongan Indramayu. This research was a quantitative research using True-Experimental Design design with Posttest-Only Control Group design. The population in this study is the entire class VII SMP Negeri 1 Balongan indramayu consisting of 11 classes with a total of 352 students. Sampling technique using Probability Sampling technique Cluster Random Sampling type obtained grade VII H as experimental group and grade VII A as control group. Instrument in this research in the form of test of skill of generic science skill student which amounted to 5 problem. Based on the research result, it was found that the average in the experimental class is 74 and the control class is 63,75. With a significant level (α) = 0.05 and degrees of freedom (db) 62 obtained tcount = 28.29 and ttable = 2,000. Because tcount> ttable, then reject Ho. This means that the 7E learning cycle model influences the generic skills of students' science on environmental pollution material in SMP Negeri 1 Balongan Indramayu.